Guide: Reporting on an Entity's Cyberse. (Aicpa Ser., 2017)
Created by the American Institute of Certified Public Accountants, this authoritative guide provides interpretative guidance to enable accountants to examine and report on an entity's cybersecurity risk management program and controls within that program. It delivers a framework which has been designed to provide stakeolders with useful, credible information about the effectiveness of an entity's cybersecurity efforts.